The Fusion of the Bologna Process, Liberal Arts Education, and Indonesian Educational Transformation Ideas in the MBKM Policy - Hidayat, Rahmad (Jurnal Pemerintahan dan Politik Lokal, 2024)
Higher education in Indonesia is undergoing a vital transformation through the presence of the MBKM (Merdeka Belajar Kampus Merdeka) policy, which combines the principles of the Bologna Process (BP) and Liberal Arts Education (LAE) to create an inclusive and dynamic learning environment. Under this context, this article aims to investigate the urgency and implications of combining the BP paradigm, LAE, and the idea of Indonesian educational transformation embedded in the MBKM policy and present the findings through a narrative overview approach that involves in-depth analysis of literature related to BP, LAE, and MBKM implementation in Indonesia. Through a narrative overview process, this article highlights the importance of academic freedom, a holistic approach, and the role of students as active agents in the learning process. The research findings confirm that MBKM is a step forward in providing relevant and responsive higher education in Indonesia. The fusion of the BP and LAE paradigms in MBKM holds a strong foundation for inclusive learning oriented towards preparing students with critical skills, adaptability and social responsibility. Thus, this article presents a complete understanding of the urgency and implications of combining the BP and LAE paradigms in MBKM and accentuates the importance of innovative interventions preparing students to become skilled and knowledgeable leaders in an era that continues to change rapidly.